Graphics, audio-visuals and interaction (GAI) based augmented reality (AR) system for symbian and android smartphone - Md. Abdullah, Al - Jubair (Universiti Malaysia Sarawak, (UNIMAS), 2012)
(Augmented Reality (AR) is a live, direct or indirect, view of a physical, real-world environment whose elements are augmented by computer-generated sensory input such as sound, video and graphics data. This research studied an open source `ARToolKitPlus' tracking library and developed Graphics, Audio-visual and Interactions (GAI) based Augmented Reality system for Symbian and Android Smartphone, which are integrated with mobile graphics module, audio video module and 3D object interaction module The GAI based mobile AR system allows the users to build the AR game applications. The development of the GAI based mobile AR system involved video capturing, image processing, mobile graphics module, audio-visual module and interactions module. Video capturing component for Symbian AR was implemented by using Symbian and video capturing component for Android AR was implemented by using Android camera API. An image library was built to perform image processing tasks. OpenGLES and PowerVR graphics API were used to build the graphics module for this system. Audio video API of Symbian and Android were used to build the GAI based audio video module. Color picking algorithm was used to build the interactions module. In addition, a mobile game application was developed to evaluate all the modules functionalities of 2D, 3D, text, animations, audio, video and 3D object interactions. This research has performed the evaluation to prove the effectiveness and efficiency of the GAI modules in the mobile game applications. The respondents generally found that the GAI modules performance in the game applications is acceptable. The result of the respondents' satisfaction in these mobile game applications indicates that the Graphics Audiovisual and Interaction (GAI) based modules in mobile AR system were successfully implemented in this research.